Effectiveness of biological nurturing on early breastfeeding problems: a randomized controlled trial - Mariarosa Milinco; Laura Travan; Adriano Cattaneo; Alessandra Knowles; Maria Vittoria Sola; Enrica Causin; Caterina Cortivo; Maura Degrassi; Francesca Di Tommaso; Giuseppa Verardi; Laura Dipietro; Maria Piazza; et al. (BMC, 2020)
Abstract Background Biological nurturing is a neurobehavioral approach to breastfeeding support that encourages women to breastfed in a relaxed, laidback position. This approach has the potential to reduce breast problems (e.g., sore nipples), making good latch easier and thus facilitating the initiation of exclusive breastfeeding. However, its effects have not been adequately investigated in a real-life situation. The aim of this randomized controlled trial was to assess the effectiveness of biological nurturing, compared to usual hospital practices, on the frequency of breast problems and on the prevalence of exclusive breastfeeding at discharge from the maternity ward, after 1 week, and at one and 4 months. Methods Open randomized parallel controlled trial carried out in a third level maternity ward (IRCCS Burlo Garofolo, Trieste, Italy) between March and December 2018. Two-hundred eight women who planned to give birth at the hospital and who expressed the intention to breastfeed were enrolled during pregnancy and randomized to receive breastfeeding support following either the biological nurturing approach or the usual care protocol based on the WHO/UNICEF 20-h course, in use at the hospital. The primary study outcome was the incidence of breast problems during hospital stay, defined as the presence of one or more of the following outcomes, collected separately: sore nipples, cracked nipples, engorgement and mastitis. The primary analysis was performed by intention to treat. The follow up lasted 4 months. Results One hundred eighty eight out of 208 women (90.3%) were included in the analysis, 90 allocated to the biological nurturing group and 98 to the usual care group. At discharge from the maternity ward, biological nurturing significantly reduced the risk of breast problems (Relative risk [RR] 0.56, 95% Confidence Interval [CI] 0.40, 0.79), including cracked (RR 0.42, 95% CI 0.24, 0.74) and sore nipples (RR 0.59, 95% CI 0.40, 0.88). No statistically significant difference was observed for exclusive breastfeeding at discharge and up to 4 months. No adverse events occurred. Conclusions The biological nurturing approach applied in the real-life situation of a third level hospital was effective in preventing breast problems. Trial registration Clinicaltrials.gov NCT03503500 . Date of First Submission: 28 March 2018.